The immediate effects of three running techniques on lower limb and trunk kinematics - dos Santos, A. F.; Nakagawa, T. H.; Serrão, F.V. (International Calgary Running Symposium, August 14-17, 2014, 2014)
It is estimated that more than 38 million Americans practice running. Approximately 56% of recreational runners present some injury every year (more than 40% involves the knee joint). Recently, it has been hypothesized that three running techniques have the potential to produce beneficial effects on the lower limb biomechanics reducing the demand on the knee joint: forefoot strike (FFOOT), increasing 10% of the step rate (10%SR) and increasing the trunk flexion (TFLEX). This study aimed to compare the immediate effects of these techniques on the trunk, hip, knee and ankle kinematics compared to usual running (USRUN) in healthy runners. Thirty-one rearfoot strike-landing runners were evaluated. The variables were collected at initial foot contact on the treadmill. For statistical analysis, it was used the MANOVA with repeated measures (á=0.05). The FFOOT resulted in a reduction in knee external rotation (P<0.001), hip flexion (P<0.001), adduction (P=0.001), internal rotation (P<0.001), greater knee adduction (P=0.016), knee flexion (P<0.001) and plantar flexion (P<0.001). The 10%SR diminished knee external rotation (P=0.001), hip internal rotation (P=0.008), hip flexion (P=0.001), and increased knee flexion (P=0,042). The TFLEX increased knee adduction (P=0.001), hip flexion (P<0.001), trunk flexion (P<0.001), and decreased plantar flexion (P=0.003). The three techniques showed clinically relevant results considering the lower limb alignment which reduces the risk of knee injury. The FFOOT can minimized the knee and hip movements in the frontal and transverse planes, the 10%SR was more sensitive to changes in the transverse plane, while the TFLEX modify the angles in the sagittal plane.